2022
DOI: 10.36263/nijest.2022.01.0330
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Effects and Vulnerability Assessment of Flooding in Udu Local Government Area, Delta State, Nigeria

Abstract: This study is based on the ecological effects and vulnerability assessment of flooding within Udu Local Government in the Delta State region. This research adopted the survey design. Five (5) flood vulnerable communities which represent the major subdivisions in Udu were investigated. Stratified random technique of sampling was used to divide the communities into quarters for effectiveness in data collection, while simple random technique was adopted in the collection of data. Data collection was on the commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…Okorie et al (2012) averred that climate variation is caused by the trend in Niger Delta Region, Nigeria Journal of Management and Social Science Research, Volume 4, Numbers 1, 2023 asymmetrical circulation of solar radiation, unique responses of the surface of the earth, oceans and atmosphere, relationships among these processes and the physical surroundings, as well as regional features. Variations in the climate of the Niger Delta region have been linked to human-caused behaviours including urban development and the burning of gas, which have reduced the ecological diversity (Efe, 2003;Kemela & Phoebe, 2021;Ndakara & Atuma, 2021). Researchers have shown that this biological diversity decline has caused the surrounding environment to become increasingly hot along with the increase in ambient temperature, which in turn has caused a large portion of sea and surrounding water bodies to evaporate at a fast rate, which has led to high spatiotemporal inconsistency of temperature and in turn have generated great environmental enigmas (Udosen, 2012;Isikwue et al, 2013;Matthew et al, 2013;Okoro et al, 2014;Igweze et al, 2014 andEgor et al, 2015;Kemela & Phoebe, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Okorie et al (2012) averred that climate variation is caused by the trend in Niger Delta Region, Nigeria Journal of Management and Social Science Research, Volume 4, Numbers 1, 2023 asymmetrical circulation of solar radiation, unique responses of the surface of the earth, oceans and atmosphere, relationships among these processes and the physical surroundings, as well as regional features. Variations in the climate of the Niger Delta region have been linked to human-caused behaviours including urban development and the burning of gas, which have reduced the ecological diversity (Efe, 2003;Kemela & Phoebe, 2021;Ndakara & Atuma, 2021). Researchers have shown that this biological diversity decline has caused the surrounding environment to become increasingly hot along with the increase in ambient temperature, which in turn has caused a large portion of sea and surrounding water bodies to evaporate at a fast rate, which has led to high spatiotemporal inconsistency of temperature and in turn have generated great environmental enigmas (Udosen, 2012;Isikwue et al, 2013;Matthew et al, 2013;Okoro et al, 2014;Igweze et al, 2014 andEgor et al, 2015;Kemela & Phoebe, 2021).…”
Section: Introductionmentioning
confidence: 99%